Development of an Addie Based Instructional Model for ELT in Early Childhood Education - Wawat Srinawati Srinawati; Syamsul Bahri; Tri Yuliastuti (International Journal of Integrated Science and Technology, 2023)
The study's main goal is to create and validate an ADDIE model-based instructional model for English Language Teaching (ELT) in early childhood classrooms as a tool for teachers to more strategically reconstruct their knowledge and experience, as well as to better design and implement their instruction. This research is developmental in nature, and it has been separated into five parts. Existing methodologies and instructional strategies are reviewed in Phase I, followed by instructional model building in Phase II, Delphi 1st round, Delphi 2nd round, and model validation in Phase V. Phase II begins with a review of relevant literature and existing strategies, followed by the creation of the first iteration of the instructional model. Following that, in phases III and IV, two rounds of Delphi were held, in which experts from various areas of the study examined the first version and eventually the final version of the instructional model was created. In Phase V, the same Delphi panelists endorsed the instructional approach for English teachers in early childhood classrooms. The instructional model elaborates the 1) representative important elements, 2) instructors' tasks recommended for the instructors, and 3) supporting techniques in relation to each phase of ADDIE. This study incorporates both the conceptual and procedural models to provide a fuller picture of the entire process. Finally, the study offers some recommendations for instructors and practitioners when it comes to selecting an instructional model, such as conducting a prior need analysis, incorporating teacher training programs, training students, continuing to research for effective teaching techniques and tools, and being open to changes, among other things. Furthermore, the study acknowledges its limitations, such as the inability to address psychological aspects due to time constraints. Finally, the report identifies areas in which more research is needed